Barriers Associated to Exclusive Breastfeeding among Women’s of Infants Under-Six Months in Ethiopia Using the 2019 Ethiopian Mini Demographic and Health Survey - Erango, Dr Markos Abiso; Kutaye, Gulilat Kurate; Gergiso, Kabtamu Tolosie (Ethiopian Journal of Reproductive Health, 2025)
Background: Exclusive breastfeeding (EBF) is a highly effective, cost-efficient intervention to reduce infant morbidity and mortality globally. It plays a vital role in improving infant immunity and supporting physical and mental development. Despite its proven benefits, the prevalence of EBF in Ethiopia remains lower than the recommended levels set by the World Health Organization (WHO). This study aims to assess the prevalence of EBF and identify the barriers affecting its practice among women with infants under six months old in Ethiopia. Methods: Secondary data from the 2019 Ethiopian Mini Demographic and Health Survey (EMDHS) were used, employing a cross-sectional study design. The sample was selected using a stratified, two-stage cluster sampling approach. In the first stage, 305 enumeration areas (EAs) were chosen, including 93 urban and 212 rural areas. In the second stage, households were selected, and 573 women were included in the analysis. A multi-level logistic regression model was employed to investigate the barriers significantly associated with EBF practices. Results: The prevalence of EBF was 59.86%, which is significantly below the WHO's recommended threshold. Considerable variation in EBF prevalence was observed across Ethiopia's regional states, with an 8.30% difference. The random intercept binary logistic regression model was the best fit for the data. The results indicated that women's age, household wealth index, education level, family size, place of delivery, antenatal care visits, residence, and mode of delivery were significant factors influencing EBF. Conclusion: The EBF prevalence of 59.86% is well below the WHO’s recommended levels. Addressing barriers to EBF requires a comprehensive approach, including shifting community attitudes, enhancing policies, and improving women's access to education and healthcare. Key stakeholders, including health workers, policymakers, and organizations such as UNICEF and WHO, should